How close is your government to its people? Worldwide indicators on localization and decentralization - Maksym Ivanyna; Anwar Shah (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper provides a unique data set on local governance. This dataset measures government decisionmaking at the local level, i.e. the level of government closest to the people. By contrast, the existing literature has focused on decisionmaking at the sub-national level. The data set covers 182 countries, and it captures institutional dimensions of political, fiscal and administrative autonomy enjoyed by local governments. These dimensions are then aggregated to develop a decentralization index and are then adjusted for heterogeneity to develop a government closeness index.
Keywords: H10; H11; H83; I31; O10; 330; localization; decentralization; fiscal autonomy; political autonomy; administrative autonomy; government accountability; trust and mistrust in governments; responsive; accountable and fair governance